2022
DOI: 10.1371/journal.pone.0273341
|View full text |Cite
|
Sign up to set email alerts
|

Plant-derived compounds effectively inhibit the main protease of SARS-CoV-2: An in silico approach

Abstract: The current coronavirus disease 2019 (COVID-19) pandemic, caused by the coronavirus 2 (SARS-CoV-2), involves severe acute respiratory syndrome and poses unprecedented challenges to global health. Structure-based drug design techniques have been developed targeting the main protease of the SARS-CoV-2, responsible for viral replication and transcription, to rapidly identify effective inhibitors and therapeutic targets. Herein, we constructed a phytochemical dataset of 1154 compounds using deep literature mining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Previous studies also reported similar findings to our study. Numerous plant-derived phytochemicals such as curcumin, gartanin, robinetin, 83 amentoflavone, gallocatechin gallate, 84 chelidimerine, rutin, fumariline, catechin gallate, adlumidine, astragalin, somniferine, 85 kaempferol, herbacetin, eugenol, 6-shogaol, 86 triacontane, hexacosane, methyl linoleate, and methyl palmitoleate, 87 cosmosiine, pelargoniding-3- O -glucose, and cleomiscosin 88 formed similar binding patterns while docking with the main protease. Another study also reported that plant-derived phytochemicals including flavan 3-ols (catechins/procyanidins), complex oligomeric procyanidins (procyanidin A3, procyanidin A4, procyanidin A1, and procyanidin B3) exhibited very good binding characteristics like our compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported similar findings to our study. Numerous plant-derived phytochemicals such as curcumin, gartanin, robinetin, 83 amentoflavone, gallocatechin gallate, 84 chelidimerine, rutin, fumariline, catechin gallate, adlumidine, astragalin, somniferine, 85 kaempferol, herbacetin, eugenol, 6-shogaol, 86 triacontane, hexacosane, methyl linoleate, and methyl palmitoleate, 87 cosmosiine, pelargoniding-3- O -glucose, and cleomiscosin 88 formed similar binding patterns while docking with the main protease. Another study also reported that plant-derived phytochemicals including flavan 3-ols (catechins/procyanidins), complex oligomeric procyanidins (procyanidin A3, procyanidin A4, procyanidin A1, and procyanidin B3) exhibited very good binding characteristics like our compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Simulations were performed using the Berendsen thermostat, accompanied by fixed pressure and temperature for 100 nanoseconds (ns) [ 61 , 62 ]. The root-mean-square-fluctuation (RMSF), root-mean-square deviation (RMSD), radius of gyration (Rg), solvent-accessible surface area (SASA), and hydrogen bond were examined through the simulation trajectory data [ 63 , 64 , 65 , 66 ]. Additionally, using the following equation, the binding free energies of the simulation snapshots were estimated using MM-PBSA (Molecular Mechanics-Poisson Boltzmann Surface Area) techniques.…”
Section: Methodsmentioning
confidence: 99%
“…The simulation was run for 100 ns at a constant temperature and pressure, along with the Berendsen thermostat, and the data of the simulation trajectories were recorded after every 100 ps [38,39]. The data of the simulation trajectories were utilized after the simulation process for the analysis of the root mean square deviation (RMSD), radius of gyration (Rg), root mean square fluctuation (RMSF), solvent accessible surface area (SASA), and hydrogen bond [40][41][42].…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%